Legitimacy and Innovation in Mining: the case of the Oro Verde Program - Sarmiento, Mariana (2013)
The paper describes how the Oro Verde Program emerged, and how it has gained recognition as an innovative program that has successfully promoted improved social and environmental practices for small scale miners. The paper describes the local and regional context where the miners from Oro Verde are from, and attempts to explain how it waspossible for two afro-colombian communities, two NGOs and a government agency to find alternative arrangements to overcome the challenges that result from the complexities of the Choco region in Colombia. The paper argues that one factor of success is the interaction among participants to create a Non-State Market Driven Governance System. In the case of the Oro Verde Program, the norms created by the international system surrounding sustainable development were necessary for allowing the NGOs to bring financial resources into the project as well as opening the doors to isolated communities in Choco to an international market that valued sustainably produced products. Similarly, the national policies surrounding Green Markets and the existence of a government research institution, made the certification process possible and legitimate. Finally, having a law that recognized land rights to afro-Colombian communities and the community councils as local authorities, as well as customary laws about natural resource use and access within these territories was key for the viability of the project. All of these organizations, working as a nested governance system, that respected and embraced different but interdependent norms and interests, were key for the consolidation of a NSMD that has resonated throughout the world and that has become an element of some afro-Colombians’ struggle to protect their rights for self-determination.